2018
DOI: 10.7752/jpes.2018.s5298
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Problem Statement. For both patients and their families, the use of medical diaries represents an up-todate approach, especially in the digital information context. In Occupational Therapy and Physical Therapy, the patient's diary acquires specific valences, overcoming the purely medical interpretation, and moving to the occupational side, which gives individualization notes of the clinical context. In the field of Sports Science, there are also many mobile applications that serve to monitor health and physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The results of this study are consistent with the results of other studies on the experimental effectiveness of the self-monitoring process by non-professional athletes using mobile technologies (Henriksen et al, 2018;Wennman et al, 2019). Despite the research data, there are many mobile algorithms that are not confirmed by experimental studies (Iconaru et al, 2018). An overabundance of the proposed mobile applications and methodological recommendations saturates the fitness market with low-quality…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results of this study are consistent with the results of other studies on the experimental effectiveness of the self-monitoring process by non-professional athletes using mobile technologies (Henriksen et al, 2018;Wennman et al, 2019). Despite the research data, there are many mobile algorithms that are not confirmed by experimental studies (Iconaru et al, 2018). An overabundance of the proposed mobile applications and methodological recommendations saturates the fitness market with low-quality…”
Section: Discussionsupporting
confidence: 84%
“…However, many amateur athletes who have not previously used the Internet fitness industry cannot optimally integrate into the fitness process through a mobile device overnight (Cho & Tian, 2019;Sushames et al, 2016). Moreover, an individual approach to the implementation of physical activity and a longer period to search for a suitable and accessible type of training are necessary (Iconaru et al, 2018;Nagovitsyn et al, 2018;Yoo et al, 2017). It should be especially noted that many fitness programs on the Internet involve special equipment and facilities, which the majority of the population of the Russian Federation do not have available.…”
Section: Introductionmentioning
confidence: 99%
“…The studies experimentally prove the positive aspects of using various mobile technologies [13]. For example, mobile digital diaries, which are used to monitor the state of health and physical fitness [14,15]. Namely, the proposed applications motivate those involved to adopt a healthy and active lifestyle [23].…”
Section: Resultsmentioning
confidence: 74%
“…Individual structural qualification characteristics of users are taken into account [13]. Not only for athletes, but also for their coaches or sports mentors, the use of digital diaries is a modern approach to physical education activities [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…There are some recent studies explicitly proposing different types of the introduction of innovative technologies in the training process of middle-aged, elderly and senile people. In particular, research works aimed at individualizing sports training based on mobile technologies [1]. They consist in taking into account the individual structural qualification characteristics of those involved, in analyzing patterns and predicting the training process of athletes of different ages and their functional and physical characteristics and their physiological characteristics [2,3].…”
Section: Introductionmentioning
confidence: 99%